2003
DOI: 10.1038/sj.onc.1206141
|View full text |Cite
|
Sign up to set email alerts
|

Identification of RUNX1/AML1 as a classical tumor suppressor gene

Abstract: Based on our previous results indicating the presence of a tumor suppressor gene (TSG), chromosome 21 was analysed for loss of heterozygosity (LOH) in 18 patients with acute myeloid leukemia (17, AML-M0; one, AML-M1). Allelotyping at polymorphic loci was performed on purified material, allowing unequivocal detection of allelic loss and homozygous deletions. Six AML-M0 patients shared a common region of LOH harboring a single gene: RUNX1 (AML1), the most frequent site of translocations in acute leukemia and a w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 53 publications
0
56
2
Order By: Relevance
“…In addition, RUNX1 point mutations were reported in sporadic and familial myeloid leukemia (Osato et al, 1999;Song et al, 1999). Subsequent studies have confirmed the occurrence of RUNX1 point mutations in AML, predominantly in the M0 subtype (Preudhomme et al, 2000;Langabeer et al, 2002;Matsuno et al, 2003;Roumier et al, 2003;Silva et al, 2003). Whereas mutations in the C-terminal domain were believed for some time to cluster within the RUNT domain, mutations in the C-terminal region, outside the RUNT domain, have also been identified, predominantly in MDS-AML (Harada et al, 2003).…”
Section: Transcriptional Dysregulation In Runx1 Leukemiasmentioning
confidence: 76%
“…In addition, RUNX1 point mutations were reported in sporadic and familial myeloid leukemia (Osato et al, 1999;Song et al, 1999). Subsequent studies have confirmed the occurrence of RUNX1 point mutations in AML, predominantly in the M0 subtype (Preudhomme et al, 2000;Langabeer et al, 2002;Matsuno et al, 2003;Roumier et al, 2003;Silva et al, 2003). Whereas mutations in the C-terminal domain were believed for some time to cluster within the RUNT domain, mutations in the C-terminal region, outside the RUNT domain, have also been identified, predominantly in MDS-AML (Harada et al, 2003).…”
Section: Transcriptional Dysregulation In Runx1 Leukemiasmentioning
confidence: 76%
“…However, the significance of the RUNX1 gene in cancer development is not fully known. Previous studies have suggested that the RUNX1 gene functions as a tumor suppressor in AML (25), and that loss of the RUNX1 gene may lead to weak differentiation and leukemia development (26). One previous study has reported that a normal expression level of RUNX1 gene inhibits cell proliferation and promotes differentiation of hematopoietic progenitor cells (21).…”
Section: Discussionmentioning
confidence: 99%
“…The level of expression of this gene was reduced on TCR stimulation and is preferentially recovered in differentiating Th2 cells. Based on previous studies that identify runx1 as a tumor suppressor (34) and affecting T cell differentiation in thymus (35), it likely plays a role in limiting Th2 cells in later stage. The Th1-selective transcription factors can also be divided into two groups based on their transcription profiles.…”
Section: Clustering Analysis Revealed That Th1͞2 Differentiation Expementioning
confidence: 99%